2011
DOI: 10.1159/000323403
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Status of Childhood Dissociative Identity Disorder: A Review of Published Research

Abstract: Background: Dissociative identity disorder (DID) remains a controversial diagnosis due to conflicting views on its etiology. Some attribute DID to childhood trauma and others attribute it to iatrogenesis. The purpose of this article is to review the published cases of childhood DID in order to evaluate its scientific status, and to answer research questions related to the etiological models. Methods: I searched MEDLINE and PsycINFO records for studies published since 1980 on DID/multiple personality disorder i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
5
15
0
Order By: Relevance
“…Middleton and Butler (1998) reported that "patients fulfilling diagnostic criteria for Dissociative Identity Disorder (DID) are regularly seen in Australian inpatient and outpatient settings" (p. 794), but their study was conducted with an adult population and there has not been a more recent update. A very recent review suggested that childhood dissociative identity disorder is rarely seen (Boysen, 2011), supporting the lack of this diagnosis in the current sample of adolescents. It is also acknowledged that clinician bias and lack of clinician education about the nature of dissociative disorders can lead to a lack of appropriate recognition and diagnosis (International Society for the Study of Dissociation, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…Middleton and Butler (1998) reported that "patients fulfilling diagnostic criteria for Dissociative Identity Disorder (DID) are regularly seen in Australian inpatient and outpatient settings" (p. 794), but their study was conducted with an adult population and there has not been a more recent update. A very recent review suggested that childhood dissociative identity disorder is rarely seen (Boysen, 2011), supporting the lack of this diagnosis in the current sample of adolescents. It is also acknowledged that clinician bias and lack of clinician education about the nature of dissociative disorders can lead to a lack of appropriate recognition and diagnosis (International Society for the Study of Dissociation, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…c) Is DID diagnosed using valid methods? Diagnosis of DID relies heavily on structured interviews, which is consistent with standard practices in psychopathology research and an improvement over the subjective clinical diagnoses that dominate the study of childhood DID (Boysen, 2011). However, the two largest samples, representing a quarter of all new cases, emerged from studies using only clinical diagnosis (Dell, 2006a(Dell, , 2006b.…”
Section: Discussionmentioning
confidence: 92%
“…Sar et al [1] have offered points of agreement and criticism concerning my review of childhood dissociative identity disorder (DID) research [2]. To begin with points of agreement, I believe they accept the most important findings from my review.…”
Section: Introductionmentioning
confidence: 91%